THE EXISTENCE OF STATE POLICY GUIDELINES IN THE PERSPECTIVE OF ORDERING THE ORDER OF LAWS AND REGULATIONS - Utami, Tanti Kirana (International Journal of Research -GRANTHAALAYAH, 2020)
The emergence of the discourse of reviving the Outlines of the State Direction (starting now referred to as GBHN) or in standard terms is known as the reformulation of the national development planning system with the GBHN model derived from the recommendations of the Indonesian MPR for the 2009-2014 period is a must. The purpose of this article is to analyze how the Outlines of State Policy Existence in the perspective of a hierarchy of laws and regulations. This article concludes that the existence of State Policy Guidelines in the Hierarchy of rules and regulations and the state administration system must always be maintained because it aims to optimize good governance that can synergize the development programs of the Central Government and Regional Governments.